Pengaruh Tingkat Pendidikan, Kesehatan, dan Pertumbuhan Ekonomi terhadap Jumlah Penduduk Miskin di Kabupaten Tanah Laut - Siti Fatimah; Chairul Sa’roni (PPJP Universitas Lambung Mangkurat, 2020)
This study aims to determine the magnitude of education level, health, and economic growth both simultaneously and partially on the number of people deficient in the District of Tanah Laut in 2010 – 2018. The data used in secondary data is sourced from the Central Statistic Agency in Tanah Laut District. The data analysis technique used in multiple regression analysis. Test results using Eviews 10 obtained the results of education level, health, and economic growth simultaneously had a significant effect on the number of people deficient in the District of Tanah Laut. Whereas partially of education level has a negative and significant impact, health is the most dominant factor. It has a positive and significant effect, and economic growth has an insignificant impact on the number of people deficient in the District of Tanah Laut.